Dense and superhydrophobic biopolymer-coated large tablet produced with energy efficient UV-curing for controlled-release fertilizer. Issue 36 (30th August 2022) - Yang, Mingchuan; Li, Shan; Zhang, Shugang; Gao, Bin; Tong, Zhaohui; Cheng, Dongdong; Chen, Denglun; Huang, Ruya; Yang, Yuechao
Abstract : This work provides an efficient UV-curing strategy for the manufacture of energy-saving, superior performance and biopolymer-coated large tablet controlled-release fertilizers. Abstract : Large tablet controlled-release fertilizers (LCRFs) can significantly improve nutrient utilization and reduce coating costs. However, traditional petrochemical coating materials are expensive and non-renewable. Furthermore, conventional heat-curing coating process is both time and energy consuming and severely impairs the controlled-release characteristics of LCRFs. To solve above problems, green processes using renewable biomaterials have become the research hotspot for the new generation of LCRFs. In this work, bio-based polyurethane acrylate (BPUA), synthesized from castor oil, was used to coat large tablet by an innovative UV-curing process for controlled-release fertilizer to overcome the drawbacks of the heat-curing process. Furthermore, BPUA was modified with polydimethylsiloxane (PDMS) and thiol grafted nanosilica (TNS) to prepare dense and superhydrophobic biopolymer-coated large tablet controlled-release fertilizer (DSBCF). The DSBCF exhibited remarkable controlled-release characteristics with a nitrogen release longevity of nearly 120 days, requiring only 4% of the coating materials. This research provides an efficient UV-curing strategy to manufacture energy saving, superior performance and biopolymer-coated LCRFs. It can solve bottlenecks that limit the development of coated fertilizers and provide theoretical and technical support for the green upgrade of the industry.